Design of novel electromagnetic principle-based sensor (2011)
This paper shows the complete design of a SAW tag based on COM and FEM simulations, both based on Comsol. Both models are used to design and characterize the interdigital transducer (IDT), reflecting gratings orreflectors and single-phase unidirectional tranducer (SPUDT) to construct the tag and obtain the final response of it. The point of both model implementation is to get a fast and accurate design algorithm for each one of the tag modules. Finally, simulations are carried in frequency and time domains for a complete SAW tag based on a common IDT and reflectors studied through the work.